Mandate of Procurement of Independent Commission for Personal Data Protection In Indonesia Reviewed from International Legal Instruments - Christine, Bella (Ridwan Institute, 2021)
Indonesia has entered the era of society 5.0 where technology is part of people's lives that have been closely attached and become a major part of people's lives themselves. In using this technology, it is not uncommon for users to first register by entering personal data. The number of cases of leaked personal data, both in private and government agencies, shows the weakness of personal data protection in Indonesia. Therefore, it is necessary to have a law that explicitly regulates and an independent commission for the protection of personal data is needed in order to monitor, take action and enforce justice for victims whose data has been leaked either intentionally or unintentionally. When compared to neighboring countries such as Malaysia and Singapore, Indonesia does not yet have an independent commission to protect and monitor personal data. In addition, referring to several international legal instruments, actually an independent commission for the protection of personal data is a necessity as well as an obligation. Therefore, in this paper, we will discuss the mandate of establishing an independent commission for the protection of personal data in terms of international legal instruments.